SWOT Analysis Of Cisande Tourism Village Assisted By Rumah Zakat SDG 8.9 Sustainable Tourism With CBT Approach - Yuza, Rico Ayatul; Lubis, Ratna Lindawati (eProceedings of Management, 2024)
Village tourism is on the rise in Indonesia, with programs like Desa Wisata Rumah Zakat actively promoting it in supported regions. This program has effectively alleviated poverty and empowered beneficiaries to participate in Rumah Zakat's initiatives. The research's primary goal is to assess the program's strengths, weaknesses, opportunities, and threats through a SWOT analysis. Strengths include increased local community involvement, streamlined decision-making processes, environmental upkeep, and support for local micro, small, and medium-sized enterprises (MSMEs). Weaknesses involve challenges in achieving program targets due to inadequate stakeholder coordination and limited community awareness. Opportunities lie in implementing new strategies and garnering support from non-governmental organizations (NGOs). Additionally, the growing tourism sector offers economic prospects for the local community. Threats encompass financial constraints, the delicate balance between tourism development and environmental conservation, and political uncertainties, which could jeopardize the program's sustainability. This research draws from management theories, sustainable empowerment principles, and a Community-Based Tourism approach to identify issues in empowered villages aligned with SDG 8.9. Qualitative methods such as interviews and field observations are employed and validated through triangulation techniques to maintain research objectivity. The study aims to develop innovative and sustainable tourism strategies in line with SDG 8.9. Keywords—UT analysis of SWOT,community based tourism, Cisande Village